2019
DOI: 10.1111/bcpt.13340
|View full text |Cite
|
Sign up to set email alerts
|

β‐LAPachone ameliorates doxorubicin‐induced cardiotoxicity via regulating autophagy and Nrf2 signalling pathways in mice

Abstract: β‐LAPachone (B‐LAP) is a naphthoquinone that possesses antioxidant properties. In the present investigation, the protective effect of B‐LAP against doxorubicin (DOX)‐induced cardiotoxicity was examined in mice. Thirty‐five mice were divided into 5 groups: control group, B‐LAP (5 mg/kg) group, DOX (15 mg/kg) group, DOX+B‐LAP (2.5 mg/kg) group and DOX+B‐LAP (5 mg/kg) group. B‐LAP was administered orally for 14 days of experimental period. A single dose of DOX (15 mg/kg) was injected intraperitoneally on day 3. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…-LAPachone (B-LAP) as a protective agent, targets AMPK/Nrf2 signaling in reducing DOX-mediated cardiotoxicity. B-LAP promotes expression of AMPK to induce Nrf2 signaling for elevating expression levels of SOX, CAT and GPX, leading to amelioration of DOX-mediated cardiotoxicity [101]. Following Nrf2 activation by phytochemicals, ROS levels decrease, preventing mitochondrial dysfunction and subsequent induction of apoptosis in cells exposed to DOX [102].…”
Section: Natural Compounds In Ameliorating Doxorubicin-mediated Toxicitymentioning
confidence: 99%
“…-LAPachone (B-LAP) as a protective agent, targets AMPK/Nrf2 signaling in reducing DOX-mediated cardiotoxicity. B-LAP promotes expression of AMPK to induce Nrf2 signaling for elevating expression levels of SOX, CAT and GPX, leading to amelioration of DOX-mediated cardiotoxicity [101]. Following Nrf2 activation by phytochemicals, ROS levels decrease, preventing mitochondrial dysfunction and subsequent induction of apoptosis in cells exposed to DOX [102].…”
Section: Natural Compounds In Ameliorating Doxorubicin-mediated Toxicitymentioning
confidence: 99%
“…β‐lapachone is a natural quinone that is isolated from the bark of the Lapacho tree ( Tabebuia avellanedae ) (Nazari Soltan Ahmad et al, 2020). B‐LAP was shown to induce anti‐inflammatory and antioxidant activities via repressing NF‐kB protein complex and activating Nrf2 transcription factor, respectively (Moon, Choi, Kim, Park, & Kim, 2007; J.‐S.…”
Section: Ncs That Protected Against Dox‐induced Cardiotoxicity Via Acmentioning
confidence: 99%
“…Also, anti‐tumor activities of B‐LAP were reported against breast cancer (Lamberti, Vittar, da Silva, Ferreira, & Rivarola, 2013). Nazari Soltan Ahmad et al examined the protective effect of B‐LAP in a mouse model of DOX‐induced cardiotoxicity; results showed that B‐LAP protective effects were mediated through regulation of the Nrf2 signaling pathway as it induced nuclear accumulation of Nrf2 and up‐regulated protein levels of HO‐1 and GST in heart samples (Figure 1) (Nazari Soltan Ahmad et al, 2020).…”
Section: Ncs That Protected Against Dox‐induced Cardiotoxicity Via Acmentioning
confidence: 99%
“…Activation of Nrf2 protects healthy cells from death. However, data from numerous studies indicate a link between Nrf2 overexpression and MDR1-associated chemoresistance in tumor cells [ 54 , 189 , 190 ].…”
Section: Molecular Mechanisms Of Mdr Development and Heparin Effects ...mentioning
confidence: 99%